2015
DOI: 10.1021/acssuschemeng.5b01385
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ionic Liquids Meet Biomolecules: A Microscopic View of Structure and Dynamics

Abstract: Room temperature ionic liquids (RTILs) and biomolecules are both paradigmatic classes of organic molecules, each consisting of a prodigious number of distinct chemical species, organized into large families of homologous compounds. Their combination is set to open new avenues for discoveries and for applications in biochemistry, biomedicine and pharmacology, food science, and nanotechnology. We provide a survey of past and current investigations of the chemical physics properties of systems made of RTILs and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
125
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 235 publications
1
125
0
Order By: Relevance
“…Since ILs have both organic/inorganic nature and high polarity, it has strong tendency to permeate through the cellular and other membranes and interact with biomolecules [19,20]. This is quite a serious concern and may cause long-term causalities to the animals and human beings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ILs have both organic/inorganic nature and high polarity, it has strong tendency to permeate through the cellular and other membranes and interact with biomolecules [19,20]. This is quite a serious concern and may cause long-term causalities to the animals and human beings.…”
Section: Introductionmentioning
confidence: 99%
“…This is quite a serious concern and may cause long-term causalities to the animals and human beings. To predict toxicity and possible fate of an IL inside a human body, several studies have been undertaken using different biomolecules [19,20]. In majority of the studies, researcher used DNA because it is a primary target of many carcinogens and a slight change in its function may lead to deadly diseases like cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the IL anions having high H‐bond basicity often significantly interfere with the native protein structure, by tempering the existing H‐bond networks . In a recent report, Benedetto et al comprehensively reviewed the current status of bio‐molecular solvation by ILs . The consequence of solvating a given protein in a specific IL is quite difficult to envisage, owing to the innumerable possible combinations of IL cations and anions and their specific/general interactions with the protein molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Franz Hofmeister, in his seminal work showed that ions have differential abilities to salt‐in or salt‐out proteins from solutions and can be ordered into a series called “Hofmeister series.” Remarkably, the same Hofmeister trend of ions tends to affect disparate phenomena related to the structural stability, function and solubility of biomolecules and thermal degradation. The salting‐out phenomenon, in fact, is a measure of the tendency of proteins to correct folding and relative ordering, while enhanced solubilization with salting‐in effect might be an indication of unfolding leading to subsequent aggregation and fibril formation . Initially, it was believed that the salts have either kosmotropic or chaotropic abilities, which could alter the structure of the essential water around the biomolecules, thereby affecting its solubility .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation